2007
DOI: 10.1080/14034940600868572
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of potential donors in the Swedish public towards information and consent procedures in relation to use of human tissue samples in biobanks: A population-based study

Abstract: The majority of the Swedish general public prefer general consent, and are thus willing to delegate some decisions to the RECs. However, preferences for information and consent procedures depend on the context, e.g. the risks for the donor and the purpose of the research. If feasible, procedures should be differentiated according to the preferences of individual donors, thus protecting the interests of both the minority and the majority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 15 publications
(25 reference statements)
6
56
1
Order By: Relevance
“…54 The most prominent concern of professionals was the complexity of the results, the uncertainty in their interpretation and concerns about the quality of information, including validity and clinical utility of genomic findings. 51,[54][55][56] The public and professionals, in general, agreed that a researcher has the obligation to disclose incidental findings; 47,50,52-54,57 however, Table 2 Data sharing/privacy protection in biobank-based genomic research: main findings Data sharing/privacy protection in biobank-based genomic research (a) Patients and the public had positive attitudes towards biobank-based genomic research and associated genomic data sharing and were mainly altruistically motivated to participate in research [24][25][26][27]29,[33][34][35][36][37][38]42 (b) Data sharing was recognized as a benefit by patients and the public 31,33,36,[40][41][42]49 (c) Patients, the public and professionals expressed privacy concerns focused on insurance, employment, 22,24,39,42,43,45 access to medical care and stigmatization 38,40,[42][43][44] (d) Benefit of data sharing for science and society outweighed potential risks; 40,43 concerns about privacy do not influence willingness to participate in biobank-based genomic research 38,…”
Section: Professionals/public N=2mentioning
confidence: 99%
See 3 more Smart Citations
“…54 The most prominent concern of professionals was the complexity of the results, the uncertainty in their interpretation and concerns about the quality of information, including validity and clinical utility of genomic findings. 51,[54][55][56] The public and professionals, in general, agreed that a researcher has the obligation to disclose incidental findings; 47,50,52-54,57 however, Table 2 Data sharing/privacy protection in biobank-based genomic research: main findings Data sharing/privacy protection in biobank-based genomic research (a) Patients and the public had positive attitudes towards biobank-based genomic research and associated genomic data sharing and were mainly altruistically motivated to participate in research [24][25][26][27]29,[33][34][35][36][37][38]42 (b) Data sharing was recognized as a benefit by patients and the public 31,33,36,[40][41][42]49 (c) Patients, the public and professionals expressed privacy concerns focused on insurance, employment, 22,24,39,42,43,45 access to medical care and stigmatization 38,40,[42][43][44] (d) Benefit of data sharing for science and society outweighed potential risks; 40,43 concerns about privacy do not influence willingness to participate in biobank-based genomic research 38,…”
Section: Professionals/public N=2mentioning
confidence: 99%
“…26,27 In contrast to patients, up to 44% of respondents from the public requested reconsent for each new study. [28][29][30] Furthermore, in one study with the public, 10% desired a possibility to decline research with their biological specimens in undesirable research fields. 30 These findings were supported by several other quantitative studies, which reported the public's desire to know the aim of research either as described in informed consent document or as approved by research ethics committee (REC).…”
Section: Content Analysis Of Articles Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer patients are generally very supportive of research on their tissue (Malone et al, 2002;Pentz et al, 1999); potential participants in cohort studies are less willing but still relatively supportive (Cousins et al, 2005;Kettis-Lindblad et al, 2005;Kettis-Lindblad et al, 2007); while the kin of potential cadaveric donors are least likely to accept donation Womack et al, 2006). The more people feel they need medical research results; the more likely they seem to be to accept donations.…”
Section: Donor Perspectivesmentioning
confidence: 99%